A Bacterial Quorum-Sensing Precursor Induces Mortality in the Marine Coccolithophore, Emiliania huxleyi - Harvey, Elizabeth L.; Deering, Robert W.; Rowley, David C.; El Gamal, Abrahim; Schorn, Michelle; Moore, Bradley S.; Johnson, Matthew D.; Mincer, Tracy J.; Whalen, Kristen E. (Frontiers in Microbiology, 2016)
Interactions between phytoplankton and bacteria play a central role in mediating biogeochemical cycling and food web structure in the ocean. However, deciphering the chemical drivers of these interspecies interactions remains challenging. Here we report the isolation of 2-heptyl-4-quinolone (HHQ), released by Pseudoalteromonas piscicida, a marine gamma-proteobacteria previously reported to induce phytoplankton mortality through a hitherto unknown algicidal mechanism. HHQ functions as both an antibiotic and a bacterial signaling molecule in cell-cell communication in clinical infection models. Co-culture of the bloom-forming coccolithophore, Emiliania huxleyi with both live P. piscicida and cell-free filtrates caused a significant decrease in algal growth. Investigations of the P. piscicida exometabolome revealed HHQ, at nanomolar concentrations, induced mortality in three strains of E. huxleyi. Mortality of E. huxleyi in response to HHQ occurred slowly, implying static growth rather than a singular loss event (e.g. rapid cell lysis). In contrast, the marine chlorophyte, Dunaliella tertiolecta and diatom, Phaeodactylum tricornutum were unaffected by HHQ exposures. These results suggest that HHQ mediates the type of interkingdom interactions that cause shifts in phytoplankton population dynamics. These chemically mediated interactions, and other like it, ultimately influence large-scale oceanographic processes.